PSEUDO SIGN OF LESER TRELAT? - Gabriella Jesslyn Evania (Yayasan Pendidikan Medika Indonesia, 2022)
Leser Trelat sign is a rare condition. Mostly, the sign appears with underlying malignant disease. A 74-year-old man presented to the hospital with multiple lesions distributed over multiple parts of the body that are increasing in number within a year. No history of malignancy within the family. Based on the anamnesis and characteristic appearance of the skin lesions, the diagnosis is still vague, therefore, we need to perform a histopathology examination. Following the skin biopsy, we perform electrocauterization to remove the other lesions. The histopathology examination results indicate that the patient's diagnosis is not a malignancy, rather he was diagnosed with seborrheic keratosis.